Development of main contractor and subcontractor relationship (MACSOR) framework for Malaysian construction projects / Siti Hamidah Abdull Rahman - Abdull Rahman, Siti Hamidah (Institute of Graduate Studies, UiTM, 2018)
The parties in construction projects such as client, consultants, contractor and subcontractors have their responsibility to participate in delivering a quality project. In the construction project environment, the conflicts between main contractor and subcontractor have been developed due to lack of communication, delivery of information on site, master and slave syndrome, poor management systems and poor supervision. Unfortunately, these problems will lead to poor on the whole management of the projects, behind schedule project delivery, create dissatisfaction between main contractor and subcontractor as well as clients and low quality of products. Therefore, it is important for contractors to maintain a good performance and reputation of work. Based on the previous research, the awareness of good relationship between contractor and subcontractor in the construction industry is low. Based on the previous research, the awareness of good relationship between contractor and subcontractor in the construction industry is low. While several studies have been conducted within the similar research boundary in the country, specific variable with growing importance in the literature, namely the human-related factors such as trust, commitment and relationship between stakeholders in the project, has not received much attention. Therefore, it is necessary to explore on the existing working relationship between contractors and subcontractors in order to develop a framework of a successful relationship between contractors and sub-contractors in the construction project. There are three stages involved in this research. Stage one; data were collected through a semi-structured interview to determine the current relationship, the challenges and the factors contributing to the good and bad relationship between main contractor and subcontractor…